2013
DOI: 10.1073/pnas.1311998110
|View full text |Cite
|
Sign up to set email alerts
|

Human circulating influenza-CD4 + ICOS1 + IL-21 + T cells expand after vaccination, exert helper function, and predict antibody responses

Abstract: Protection against influenza is mediated by neutralizing antibodies, and their induction at high and sustained titers is key for successful vaccination. Optimal B cells activation requires delivery of help from CD4 + T lymphocytes. In lymph nodes and tonsils, T-follicular helper cells have been identified as the T cells subset specialized in helping B lymphocytes, with interleukin-21 (IL-21) and inducible costimulatory molecule (ICOS1) playing a central role for this function. We followed the expansion of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 28 publications
(46 reference statements)
10
76
1
Order By: Relevance
“…3B), whereas the percentage of naive T FR (CD45RO 2 CD45RA + ) decreased significantly after 1 and 7 d (p = 0.01, data not shown). In line with other groups (21,22), we confirmed a significant increase in circulating T FH after vaccination (all time points, p , 0.001; Fig. 3C).…”
Section: Influenza Vaccination Boosts the Number Of Circulating T Frsupporting
confidence: 89%
“…3B), whereas the percentage of naive T FR (CD45RO 2 CD45RA + ) decreased significantly after 1 and 7 d (p = 0.01, data not shown). In line with other groups (21,22), we confirmed a significant increase in circulating T FH after vaccination (all time points, p , 0.001; Fig. 3C).…”
Section: Influenza Vaccination Boosts the Number Of Circulating T Frsupporting
confidence: 89%
“…1 T follicular helper cells are specialized for providing cognate B cell help and after influenza vaccination, it is the induction of these cells, rather than preexisting frequencies, that is associated with antibody induction (28,29). Interestingly, work in animal models revealed that IL-2 suppresses the differentiation of T follicular helper cells and negatively impacts influenza-specific long-lived antibody responses, a finding consistent with our observation (30,31).…”
Section: Il-21supporting
confidence: 88%
“…For example, blocking IL-21, ICOS, or CD40L with mAbs might increase either T-cell responsive infections or the rate of leukemia relapse as a result of dampening of peripheral immune surveillance mechanisms. Finally, our discovery that Tfh cells are upregulated in murine cGVHD warrants investigation of this cell population in the peripheral blood 35 of cGVHD patients. If correlations are noted with cGVHD onset or severity, Tfh cells could be targeted, as we have done in this study, which may prove useful for treating or perhaps preventing cGVHD in the clinic.…”
Section: Cd5mentioning
confidence: 99%